Implementasi Manajemen Personalia di Pesantren Terpadu Al-Kahfi Bogor - Iksan Kasmudi Satiran; Maemunah Sa'diyah (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2022)
Islamic boarding schools play a major role, namely, as motivators, innovators, and community dynamists so that the relationship between pesantren and the community becomes harmonious, as a result, the existence and presence of Islamic boarding schools in community empowerment become stronger. The purpose of this journal is to see the success of the Al-Kahfi Islamic Boarding School in implementing personnel management with reference to seven main activities, namely recruitment (personnel procurement), personnel development and development, personnel promotion and transfer, compensation for personnel, personnel welfare, personnel evaluation, termination of employment. employment relationship (PHK). This type of research is field research, namely research conducted with the direct aim of excavating and researching data relating to the effectiveness of the implementation of personnel management and what factors influence the implementation of personnel management at the Al-Kahfi Integrated Islamic Boarding School in Bogor. This research was conducted in September 2021. The results of the study after conducting interviews and collecting related data, the Al-Kahfi Integrated Islamic Boarding School has implemented all the main activities of personnel management in a well-managed and managed manner.AbstrakPesantren memegang peranan utama yaitu sebagai motivator, inovator, dan dinamisator masyarakat sehingga hubungan pesantren dengan masyarakat menjadi harmonis, hasilnya keberadaan dan kehadiran lembaga pesantren dalam pemberdayaan masyarakat menjadi semakin kokoh. Tujuan dari jurnal ini adalah melihat keberhasilan Pesantren Terpadu Al-Kahfi dalam menerapkan manajemen personalia dengan mengacu kepada tujuh kegiatan utama yaitu rekrutmen (pengadaan personalia), pembinaan dan pengembangan personalia, promosi dan mutasi personalia, kompensasi bagi personalia, kesejahteraan personalia, evaluasi personalia, pemutusan hubungan kerja (PHK). Jenis penelitian ini adalah penelitian lapangan (Field Research), yakni penelitian yang dilakukan dengan tujuan langsung kelapangan untuk menggali dan meneliti data yang berkenaan dengan efektivitas penerapan menejemen personalia dan Faktor apa saja yang mempengaruhi penerapan manajemen personalia di Pesantren Terpadu Al-Kahfi Bogor. Penelitian ini dilakukan pada bulan September 2021. Hasil penelitian setelah melakukan wawancara dan pengambilan data terkait maka Pesantren Terpadu Al-Kahfi sudah mengimplementasikan semua kegiatan utama manajemen personalia dengan baik dan terkelola.